Entanglement generation using a controlled-phase gate for time-bin qubits. (24th August 2018) - Lo, Hsin-Pin; Ikuta, Takuya; Matsuda, Nobuyuki; Honjo, Toshimori; Takesue, Hiroki
Abstract: Quantum logic gates are important for quantum computation and quantum information processing in numerous physical systems. Although time-bin qubits are suitable for quantum communication over optical fiber, many essential quantum logic gates for them have not yet been realized. Here, we demonstrated a controlled-phase (C-Phase) gate for time-bin qubits that uses a 2 × 2 optical switch based on an electro-optic modulator. A Hong–Ou–Mandel interference measurement showed that the switch could work as a time-dependent beam splitter with a variable splitting ratio. We confirmed that two independent time-bin qubits were entangled as a result of C-Phase gate operation with the switch.